Government's participation in the Agribusiness Information System: Ornamental Fish Fishermen's Income will "Increase" - Hendarto, Totok; Hiat, Ponia Sanket (Revenue Journal: Management and Entrepreneurship, 2024)
Surabaya is the primary hub of economic development for Gerbangkertosusila due to its significant contribution to the Gross Regional Domestic Product (GRDP) compared to other districts/cities. Hence, Surabaya possesses considerable potential that can be harnessed for regional development and catalyzes economic growth in several areas. The aquaculture industry in Surabaya can cultivate salty water in an area of 3,139,661 hectares and freshwater in 487,536 hectares. Freshwater cultivation encompasses several methods, including earthen ponds, concrete ponds, and tarpaulin ponds, popular among novice individuals seeking to develop ornamental fish. Betta fish farming is financially the most lucrative form of fish breeding, as it can be conducted in tarpaulin ponds with minimal capital. Nevertheless, this enterprise must generate optimal earnings due to its comparatively elevated and consistently steady prices. The involvement of regional and national governments is attributed to their endeavours to foster the growth of the betta fish industry. This study examines the government's participation in developing the betta fish industry in Surabaya. It will employ qualitative methodologies to understand the current scenario comprehensively by reviewing a detailed and thorough depiction of the situation in its natural context. The researchers conducted interviews as a component of focused sampling. The sources of information were refined based on the researcher's assessment, and comprehensive interview findings were gathered. The study participants consisted of marine ornamental fish providers, while the institutional members were selected from the Department of Fisheries and Agriculture and other Natural Resources Protection Centers. The findings indicate that the regional government of Surabaya has undertaken the initiative to identify specific locations as suppliers of Betta fish. The essay will address the central government's resolve to transform the city of Surabaya into a fishery cultivation village. The primary responsibility of the government is to facilitate and support the operations and infrastructure of Betta fish cultivators. The collaboration between programs from each agency is essential to ensure the efficient functioning of the Betta fish industry.